2006
DOI: 10.1186/1471-2458-6-274
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum practices of puerperal women and their influencing factors in three regions of Hubei, China

Abstract: Background: 'Sitting month' is a Chinese tradition for women's postpartum custom. The present study aims to explore the postpartum dietary and health practices of puerperal women and identify their influential factors in three selected regions of Hubei, China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 5 publications
6
71
3
4
Order By: Relevance
“…In a study conducted in China, dietary behaviours of about 2000 women during the postpartum period were assessed using an intervieweradministered questionnaire and an FFQ. In that study, fish and rice wine were frequently consumed by the Chinese participants during the postpartum period (22) . Furthermore, 78?8 % of the participants never ate fruit during this period (22) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in China, dietary behaviours of about 2000 women during the postpartum period were assessed using an intervieweradministered questionnaire and an FFQ. In that study, fish and rice wine were frequently consumed by the Chinese participants during the postpartum period (22) . Furthermore, 78?8 % of the participants never ate fruit during this period (22) .…”
Section: Discussionmentioning
confidence: 99%
“…In that study, fish and rice wine were frequently consumed by the Chinese participants during the postpartum period (22) . Furthermore, 78?8 % of the participants never ate fruit during this period (22) . In another study conducted in Malaysia (information gathered through interviews with informants), Malay women indicated that eggs and beef were generally avoided during the postpartum period (5) as was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Fatores culturais, como os tabus alimentares, influenciam negativamente a promoção do aleitamento materno resultando no desmame precoce 5,6,7 . A palavra tabu, segundo o minidicionário Aurélio 8 significa aquilo que está sujeito a imposições, restrições ou escrúpulos injustificados ou infundados.…”
Section: Introductionunclassified
“…As mães que sofrem uma forte influência cultural, geográfica, familiar e socioeconômica do meio em que vivem, geralmente acabam aceitando certos tabus como forma de entenderem alguns resultados como do "leite fraco", "leite que não sustenta", choro excessivo do bebê após as mamadas, problemas nas mamas, entre outros 3,5,6,7,12 . Para Lima 13 , faz-se necessário a intensificação das ações de incentivo e apoio ao aleitamento materno e para isso, os fatores que influenciam o aleitamento materno devem ser considerados na operacionalização destas ações.…”
Section: Introductionunclassified
“…It lasts approximately 6 weeks or until the reproductive organs and other physiological state of the mother returns to their normal state (10) . It is a period which begins after delivery of the baby and ends when the mother's body has returned as closely as possible to its pre-pregnant state (12) (6) .…”
Section: Introductionmentioning
confidence: 99%